The Concept of “Steppe” in the Novel-Chronicle by A. M. Amur-Sanan “Mudreshka’s Son” - Galina B. Esenova (Монголоведение)
Introduction. The article is devoted to the concept of “steppe”, which is important for the Kalmyks' worldview. The purpose of the article is to study the implementation of the concept of “steppe” in a literary text. Tasks: a) identification and comparison of the meanings of the verbalizers of the concept “steppe” in the Russian and Kalmyk languages; b) analysis of the representation of the concept «steppe» in the text of the novel-chronicle by A. M. Amur-Sanan “Mudreshka’s Son”. Material: the text of the novel-chronicle by A. M. Amur-Sanan “Mudreshka’s Son”, written in Russian in 1925. Research methods: lexical and semantic analysis of linguistic units, comparative analysis of the linguistic data obtained. Results. The verbalizers of the concept of “steppe” in Russian are the lexemes “steppe” and “field”, in Kalmyk — teg, köödä, keer. Common semes of the concept actualizers in the Russian and Kalmyk languages are ‘vastness’ and ‘desolation’. Conclusions. The text of the chronicle novel uses a variety of visual and expressive means of the Russian language, revealing the characteristic features of the concept “steppe”. “Steppe” is described as a type of terrain characterized by vastness, desolation and monotony. Such a deserted, boundless, uninhabited space contributes to the formation of a feeling of loneliness, uselessness, abandonment in the hero's mind, affects his psychological state. This gives reason to believe that in the chronicle novel by A. M. Amur-Sanan “Mudreshka’s Son”, “steppe”, artistically meaningful, becomes a topos that affects the psychological state of the hero.